Congenital glucose-galactose malabsorption - A case report - Lee, Way Seah; Goh, Adrian Yu Teik (Faculty of Medicine, University of Malaya, 1997)
We report a case of congenital glucose-galactose malabsorption (GGM) in a Malay male infant who presented with protracted diarrhoea, severe metabolic acidosis. and marked hypernatraemic dehydration since the third day of life whilst on breast feeding. He was severely marasmic, requiring total parenteral nutrition to improve the precarious nutritional status. The course of illness was complicated by Staphylococcal septicaemia and catheter related endocarditis which was eradicated by a six-week course of vancomycin and fusidic acid. Subsequent carbohydrate tolerance tests showed impaired absorption of oral glucose but normal absorption of fructose. The child tolerated fructose-based modular feed well and had normal development. At fourteen months of age he still had failure to thrive despite an adequate calorie intake and normal appetite.